Influence of environmental variables on the species richness and occurrence of anuran species in areas planted with sugarcane in central Brazil - Assis, Rhayane A. [UNESP]; Benvindo-Souza, Marcelino; Araújo-Santos, Cirley G. [UNESP]; Borges, Rinneu E.; Vieira, Thiago B.; de Souza Santos, Lia Raquel; de Oliveira, Classius [UNESP] (Springer Nature, 2025)
Agricultural activities that alter natural habitats are among the main causes of the current decline in anuran species. In recent decades, the global expansion of sugarcane cultivation has raised concerns about its environmental consequences. In these areas, water bodies that anurans use as breeding sites face chemical contamination and changes to the surrounding landscape due to human activities. In this study, we evaluate the species richness of anurans in a region of the Brazilian Cerrado savanna dominated by sugarcane production, and we identify how environmental variables influence species occurrence patterns. We recorded a total of 31 species in the study area. Dendropsophus nanus preferred larger water bodies with greater depth and more vegetation along the edges. Scinax fuscovarius, Scinax fuscomarginatus, and Boana albopunctata were associated with sites that had higher pH levels. S. fuscomarginatus, B. albopunctata, Physalaemus nattereri, and Boana raniceps tended to occur in areas with a higher percentage of natural vegetation and higher temperatures. Additionally, Dendropsophus minutus and Physalamus cuvieri were more abundant in water bodies with internal vegetation and higher nitrogen levels, while Leptodactylus fuscus was associated with areas with more dissolved oxygen and phosphorus. Our findings highlight the complexity of anuran species’ responses to anthropogenic impacts and underscore the need for systematic monitoring of water bodies near farmland, especially around crops like sugarcane.
Keywords: Agriculture; Amphibians; Anthropogenization; Cerrado; Environmental variables